Efektivitas self-determination theory dalam perilaku pemecahan masalah matematis siswa - Rafiq Zulkarnaen; Redo Martila Ruli (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Providing mathematical problems to students is the core of the process and product of learning at school. This study aims to examine the profile of the process of mathematical problem solving behavior and the profile of the level of self-determination of eighth grade students based on the level of mathematical ability, examining the relationship between Self-determination theory (SDT) and problem solving behavior, in terms of each dominant SDT aspect against the level of mathematical ability. A case study was used in this research, with multiple cases and multiple analyses. The instruments in this study consisted of mathematical problem solving ability test questions and questionnaires. The research subjects used in this study were five students of class VIII at one public junior high school in Bandung City who were taken by simple randomization, with the determination based on initial mathematical ability in the High, Medium, and Low categories. Based on the results and discussion, it is found that conceptual knowledge and procedural knowledge do have a significant influence on students in solving mathematical problems, However, the role of each aspect of SDT (interest, motivation, and confidence) also has a big impact on students ability to solve mathematical problems.